Flow over a stretching sheet in a micropolar fluid with radiation effect - Nor Azizah Yacob,; Anuar Ishak, (Penerbit Universiti Kebangsaan Malaysia, 2010)

(untitled)
Boundary layer flow and heat transfer characteristics induced by a linearly stretching sheet immersed in an incompressible micropolar fluid with prescribed surface heat flux in the presence of radiation effect is investigated. The governing system of partial differential equations is first transformed into a system of ordinary differential equations using similarity transformation, which are then solved numerically using the Runge-Kutta-Fehlberg method. The velocity, angular velocity and temperature profiles with the effects of various physical parameters are presented graphically. It is found that the heat transfer rate at the surface decreases in the presence of radiation